Analisis Kebijakan Otoritas Jasa Keuangan (OJK) Terkait Dualisme Hukum Antara Peraturan Pemerintah Nomor 45 Tahun 1995 tentang Penyelenggaraan Kegiatan di Bidang Pasar Modal (PP 45 Tahun 1995) dengan Peraturan Otoriras Jasa Keuangan Nomor 3/POJK.04/2021 t - Djayanti; Ariawan Gunadi (CV Rewang Rencang, 2024)
This research aims to examine the OJK's policy on the dualism of administrative regulations applicable to the financial services sector, particularly the Capital Market sector, namely Government Regulation Number 45 of 1945 and POJK 3 of 2021, where for about 21 months, both regulations govern the same matters and are in effect, but there are no provisions related to transitional regulations. This results in a lack of legal certainty regarding the basis used by the OJK. In addition, there are significant differences in regulations, including those related to the nominal Administrative Sanction in the form of fines for violations of late report submission and/or violations of not submitting reports. The research method used is a combination of normative and empirical legal research methods, involving critical analysis of PP 45 of 1945 and POJK 3 of 2021, and relating them to Law Number 12 of 2011 on the Formation of Legislation (Law 12 of 2011), in conjunction with legal theories and legal practices in society. The results of this study indicate that although the existing legal framework is quite strong and comprehensive, its implementation effectiveness still faces various challenges. The main obstacles include inconsistencies in legal regulations, where there are significant differences in the nominal administrative sanctions in the form of fines for late report submissions and failure to submit reports between Government Regulation No. 45 of 1945 and Financial Services Authority Regulation No. 3 of 2021 in the oversight of the Capital Market sector. This study aims to recommend strengthening the existing regulations to accommodate the significant differences in the nominal administrative sanctions in the form of fines.